Pod production, and dasometric variables, of the tree Senna spectabilis (Fabaceae) in a tropical dry forest - Duarte-Vargas, Jesús H. (2021)
Introduction: Senna spectabilis is a multipurpose pantropical tree, used in agroforestry systems. Objective: To determine pod production (Pp) and their relationship with dasometric variables in S. spectabilis in the tropical dry forest. Methods: From August 2016 to February 2017, thirty trees in production stage were randomly selected. The random selection was formed of the more isolated trees from the total dispersion. The trees were monitored at the beginning and end of the study period, to determine dasometric measurements such as total height (Th), height to the first branch (Hb), crown height (Ch), Stem diameter (at 0.2 m height from the ground) (Db), crown diameter (Cd), and crown volume (Cv) measured. Pods were harvested by the researcher with cutting and height cutting tongs when their color began to change. Pearson correlations and univariate and multivariate regression analyses were performed between the dasometric variables and pod production. The potential number of trees/ha (NPa) was calculated by determining the occlusion percentage (Op) and the shadow area/tree (Ca); to estimate the production potential of fruits/ha, the production of fruits/tree was multiplied by (NPa). Results: Th was 6.16 ± 1.23 m, Hb 2.75 ± 0.52 m, Ch 3.41 ± 0.98 m, Db 20.43 ± 4.80 cm, Cd 7.46 ± 1.20 m and Cv 108.43 ± 61.38 m3/tree. There was a significant positive correlation between Hb, Cd, Db, with Pp of 0.592**, 0.592**, and 0.446* respectively. Pp was 32.73 ± 16.13 kg/tree and the dry matter production (MSP) was 17.84 ± 8.80 kg/tree. The result of the multivariate regression indicated that the second-order polynomial model presented best goodness of fit. Op was 73.4 7.92 %, the cup area was 49.3 m2/tree, Ca was 36.2 m2/tree, and NPa was 83 trees. Conclusions: The production of fresh pods/ tree in the S. spectabilis presents a potential in its availability as feed for ruminant or seed production. The potential production of pods in silvopastoral with S. spectabilis could be 2.72 t/ ha, and 1.64 t/ ha of dry pods, this shows the importance of trees and of pods production and nutritional contribution obtained for dry ecosystems.